1998
DOI: 10.1002/(sici)1097-4547(19980715)53:2<187::aid-jnr7>3.0.co;2-3
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of acute experimental allergic encephalomyelitis by intraperitoneal administration of synaptosomal antigens

Abstract: The effect of a synaptosomal fraction isolated from bovine brain was examined on acute experimental allergic encephalomyelitis (EAE) in Wistar rats. Intraperitoneal administration of the animals with low doses of saline-soluble synaptosomal antigens 10 and 3 days previous to the active induction of the disease was an effective way of suppressing EAE. This treatment diminished the incidence and severity of EAE, reverted the appearance of central nervous system histological and biochemical alterations, and produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 0 publications
0
14
0
Order By: Relevance
“…22 Briefly, 1.25 × 10 6 cells per ml were cultured in a total volume of 200 µl per well of cRPMI with 0.5 µg ml −1 concanavalin A (Con A) in the presence or absence of ABL (0.25-1 µg ml −1 ) for 4 days at 37°C, 5% CO 2 . 22 Briefly, 1.25 × 10 6 cells per ml were cultured in a total volume of 200 µl per well of cRPMI with 0.5 µg ml −1 concanavalin A (Con A) in the presence or absence of ABL (0.25-1 µg ml −1 ) for 4 days at 37°C, 5% CO 2 .…”
Section: Proliferation Measurement Of Mononuclear Cells (Mnc)mentioning
confidence: 99%
“…22 Briefly, 1.25 × 10 6 cells per ml were cultured in a total volume of 200 µl per well of cRPMI with 0.5 µg ml −1 concanavalin A (Con A) in the presence or absence of ABL (0.25-1 µg ml −1 ) for 4 days at 37°C, 5% CO 2 . 22 Briefly, 1.25 × 10 6 cells per ml were cultured in a total volume of 200 µl per well of cRPMI with 0.5 µg ml −1 concanavalin A (Con A) in the presence or absence of ABL (0.25-1 µg ml −1 ) for 4 days at 37°C, 5% CO 2 .…”
Section: Proliferation Measurement Of Mononuclear Cells (Mnc)mentioning
confidence: 99%
“…The clinical analysis of the different groups of animals sensitized to induce EAE is summarized in Table I. As shown previously (Degano et al, 1998; Ditamo et al, 2005), about 80% of animals of the control group (treated with vehicle alone) showed the characteristic signs of the disease. Despite this fact, the rest of the animals manifested a subclinical state of disease, with reactivity to MBP and histological alterations.…”
Section: Resultsmentioning
confidence: 65%
“…These results clearly indicate that the genetic coupling of synapsin C domain to LTB constitutes a valid alternative model based probably on bystander suppression of immune response to a structurally unrelated antigen. The protective effect of LTBSC parallels the EAE suppression achieved by administration of a purified synaptosomal fraction (Degano et al, 1998, 2004).…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Intravenous, intragastrointestinal and oral administration of MBP are other strategies of suppressing EAE without the use of IFA (see Degano et al . for review) 11 . We have previously shown that i.p.…”
Section: Introductionmentioning
confidence: 99%